MODELING OF DROPLET DYNAMIC AND THERMAL HISTORIES DURING SPRAY FORMING .1. INDIVIDUAL DROPLET BEHAVIOR - Grant, P; Cantor, B; Katgerman, L (1993)
A computer model has been developed to describe the in-flight dynamic and thermal histories of gas atomised droplets as a function of distance during spray forming. Modifications of the model have been used to evaluate the relative importance of different physical assumptions in controlling droplet cooling and solidification behaviour, and ultimately the evolution of spray formed billet microstructures. Gas atomised droplet dynamic and thermal behaviour is strongly affected by the distribution of droplet diameters in the two phase spray and the momentum transfer between the droplets and the atomising gas, but is relatively unaffected by the details of the droplet solidification mechanism. © 1993.